2017
DOI: 10.1126/sciadv.1602573
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of 2C helicase from enterovirus 71

Abstract: Structure of EV71 2C unveils the structural basis of the functional mechanism of carboxyl terminus–mediated self-oligomerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(173 citation statements)
references
References 33 publications
(43 reference statements)
6
159
0
Order By: Relevance
“…treat an immunocompromised child with chronic enteroviral encephalitis 89 , underscoring the potential of drug repurposing in antiviral therapy. The recently elucidated structure of EV-A71 2C 90 will likely encourage soaking or co-crystallization studies and provide more insight into the mode of action of 2C inhibitors, allowing optimization through structure-guided drug design. In addition, inhibitors of host factors, including compounds targeting PI4KB and OSBP, inhibit a broad range of enteroviruses.…”
Section: Heterogeneous Nuclear Ribonucleoprotein Cmentioning
confidence: 99%
“…treat an immunocompromised child with chronic enteroviral encephalitis 89 , underscoring the potential of drug repurposing in antiviral therapy. The recently elucidated structure of EV-A71 2C 90 will likely encourage soaking or co-crystallization studies and provide more insight into the mode of action of 2C inhibitors, allowing optimization through structure-guided drug design. In addition, inhibitors of host factors, including compounds targeting PI4KB and OSBP, inhibit a broad range of enteroviruses.…”
Section: Heterogeneous Nuclear Ribonucleoprotein Cmentioning
confidence: 99%
“…Compared with 2D microelectrodes, highly ordered 3D‐structured materials for microbatteries can provide a maximum specific surface area, multiple nanostructures, and shorter ion transmission distances, which lead to a higher areal energy density, superior power density, and outstanding mechanical properties . Furthermore, the facilitation of 3D microbatteries relies on emerging thin‐film deposition techniques . Among these advanced microfabrication strategies, the ALD technique can produce highly protected, uniform, and reproducible atomic‐scale films on high‐aspect‐ratio substrates by precisely control over the thickness, homogeneity, and structure, as shown in Table .…”
Section: Advanced Electrode Engineering For Novel Sibs By Aldmentioning
confidence: 99%
“…Recently, some brief reviews have reported the development of micro‐LIBs by using ALD . Herein, we focus on certain critical studies about ALD‐designed micro‐SIBs.…”
Section: Advanced Electrode Engineering For Novel Sibs By Aldmentioning
confidence: 99%
“…It is composed of a N-terminal membrane binding domain, a central ATPase domain, a cysteine-rich domain and a C-terminal helical domain [ 20 ]. We recently determined the crystal structure of a soluble portion of 2C helicase from human enterovirus 71 (EV71) [ 21 ], the first high-resolution 2C structure in Picornaviridae . The ATPase domain of EV71 2C exhibits the structural characteristics of superfamily 3 (SF3) helicases.…”
Section: Introductionmentioning
confidence: 99%